2021
DOI: 10.3390/ijerph18105118
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Measurement Invariance of the Maslach Burnout Inventory–General Survey in Colombia

Abstract: The Maslach Burnout Inventory–General Survey (MBI-GS) is a widely used scale that measures burnout in the general professions. Debate persists regarding the factor structure of the MBI-GS, and there is scarce empirical evidence about the reliability, validity, and measurement invariance of the MBI-GS in Spanish-speaking samples. Moreover, the psychometric properties of the MBI-GS have not been analyzed in Colombia. This study aimed to analyze the internal consistency, factor structure, measurement invariance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
3
14
0
4
Order By: Relevance
“…Taken as a whole, the present study provides good support for the psychometric properties of the DASS in university students in Hong Kong. It is noteworthy that the analyses used in this study are consistent with those reported in the field [41][42][43]61,62].…”
Section: Discussionsupporting
confidence: 83%
“…Taken as a whole, the present study provides good support for the psychometric properties of the DASS in university students in Hong Kong. It is noteworthy that the analyses used in this study are consistent with those reported in the field [41][42][43]61,62].…”
Section: Discussionsupporting
confidence: 83%
“…Participants responded to the 22 items of the MBI using a 7-point Likert scale that ranged from 0 (Never) to 6 (Every day). While there has been a debate about the factor structure of the MBI, there has also been strong support for the proposed three-factor structure in dif-ferent contexts (e.g., Colombia [25]; Spain [26]). In addition, Schaufelli and colleagues [27] confirmed the validity of the three-factor structure of the MBI and found that the emotional exhaustion and depersonalization dimensions were able to distinguish between burned out and non-burned out workers.…”
Section: Instrumentsmentioning
confidence: 99%
“…10.3389/fpsyt.2023.1145606 used (40). In the present study, the Chinese version of MBI-GS (41) was adopted to investigate burnout among pharmacists.…”
Section: Participantsmentioning
confidence: 99%